Peranan Pondok Pesantren Di Era Digital - Abdul Muid (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2019)
Islamic Boarding School Education is the most fun for students in this digital age because Islamic Boarding School education is very convenient for the development of children's mental health in order to achieve world education goals and the hereafter. To answer the challenges of parents, the Islamic Boarding School in this era was equipped with a very complete formal education. Especially to form an Islamic character that has added values ​​in creating children with the character of al-akhlaq al-karimah. For parents, God willing, the world of pesantren is an educational institution that will bring prosperity and safety to their children, not only welfare in the world, but isya Allah the welfare of life in the hereafter. Herein lies the importance of the Research on the Role of Islamic Boarding Schools in the Digital Era, this is a solution for parents of students who will leave their children in Islamic Boarding Schools. There used to be a lot of assumptions by parents who left their children at the Islamic boarding school to only print Modin and Kyai, but that assumption was completely eroded by the reality in the field which was able to prove, that many children of Islamic Boarding School graduates who entered State Universities, such as UNAIR, ITS , Universitas Brawijaya Malang, UGM, and so on can be anything, so the assumption disappears on its own. So that empirical evidence is able to change the paradigm of students 'parents' thinking to increasingly love Islamic boarding schools. In the community's old-fashioned thinking, they consider boarding schools are only to accommodate children who are not achievers, (Naughty), then Islamic Boarding Schools in this Era, the assumption disappears by itself, because Islamic boarding school graduates are able to displace the outstanding state schools, because pesantren are managed by modern management and are increasingly loved and loved by the community, except pesantren which apply special management of the salaf method).